2010
DOI: 10.1007/s13280-010-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Process Based Modelling of Phosphorus Losses from Arable Land

Abstract: Improved understanding of temporal and spatial Phosphorus (P) discharge variations is needed for improved modelling and prioritisation of abatement strategies that take into account local conditions . This study is aimed at developing modelling of agricultural Phosphorus losses with improved spatial and temporal resolution, and to compare the accuracy of a detailed process-based model with a rainfall-runoff coefficient-based model. The process-based SWAT model (Soil and Water Assessment Tool) was implemented f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…In summary, our results support the findings of Ekstrand et al [58], who applied SWAT to model the TP losses in five catchments in central Sweden. Overall, Ekstrand et al [58] observed that obtaining satisfactory results for a validation period often depends on whether the range of hydroclimatological conditions is similar (as in calibration).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In summary, our results support the findings of Ekstrand et al [58], who applied SWAT to model the TP losses in five catchments in central Sweden. Overall, Ekstrand et al [58] observed that obtaining satisfactory results for a validation period often depends on whether the range of hydroclimatological conditions is similar (as in calibration).…”
Section: Discussionsupporting
confidence: 91%
“…However, the reported values of PBIAS for most of the gauges are within the ranges of satisfactory performance for discharge (+/-25%) and the NO 3 -N and TP loads (+/-70%) [49]. In summary, our results support the findings of Ekstrand et al [58], who applied SWAT to model the TP losses in five catchments in central Sweden. Overall, Ekstrand et al [58] observed that obtaining satisfactory results for a validation period often depends on whether the range of hydroclimatological conditions is similar (as in calibration).…”
Section: Discussionsupporting
confidence: 89%
“…In the short term, Nasr et al (2005) recommended using SWAT for TP load estimation. The SWAT model recently showed good potential for predicting TP losses from arable land in a Swedish study by Ekstrand et al (2010) (Table 4). TOPMODEL is a process based semidistributed catchment model (Irvine et al 2005) in which the major factors affecting runoff generation are the catchment topography and the soil transmissivity, which diminishes with depth (Parsons et al 2001).…”
Section: Physically-based Modelsmentioning
confidence: 99%
“…Similarly, Pionke et al (2000) showed that 90% of the P export from an agricultural watershed in the USA occurred during storm flow, which represented 10% of the time. Ekstrand et al (2010) observed that in a >800 km 2 large catchment, 76% of the annual stream TP transport was discharged during 18 days in December and January. Such sudden events will have a significant impact on P transport from arable lands.…”
Section: Dynamics Of P Transportmentioning
confidence: 99%